My Booky Wook - Brand, Russell, 1975- (London Hodder, 2008)
The controversial, unexpurgated, and hilarious life story of the nation's hottest comedian - in his own words.
Include Color Illustration
Keywords: Brand, Russell, 1975- -- Comedians -- Television personalities